Employee Productivity Analysis in the Production Department at PT. "X" - Alam Avrianto; Irfan Rizky Gumilar (Sainteks: Jurnal Sain dan Teknik, 2022)
Productivity is an important aspect because it will affect the sustainability of an organization/company, as well as PT. X. Based on the results of data collection, it is seen that there is a decrease in production productivity shown by the amount of production that is below the target. The purpose of this research is to analyze the causes of the decline in productivity. This study uses quantitative and descriptive methods in measuring the dimensions of employee productivity where the research data used is population data which is all employees in the production section. Based on the results of the study, it is known that the decrease in productivity is caused by the poor attitude and behavior of employees at work. This is indicated by the presence of other movements in addition to the core movement in making products such as using a mobile phone, chatting, etc. at work. Although the majority of the dimensions can be said to be good but with the lack of good attitudes and behavior of employees, it has a very large influence on the productivity of the company.